Introduction to electronics - Gates, Earl D. (Delmar Cengage Learning, 2012)
This book is intended for first year students or users to stimulate their interest in electronics, whether they are in high school, college or the field, and will provide them with a fundamental background in electronics that they need to succeed in today's increasingly digital world.